Lower fitness levels, higher fat-to-lean mass ratios, and lower cardiorespiratory endurance are more likely to affect the body mass index of Saudi children and adolescents - Said, Mohamed Ahmed; Alhumaid, Majed M.; Atta, Ibrahim I.; Al-Sababha, Khairi Mahmoud; Abdelrahman, Mohamed Abdelmoneim; Alibrahim, Mohammed Shaab (Frontiers in Public Health, 2022)
Background Several studies suggest that health-related physical fitness may play a prominent role in preventing obesity in children and adolescents. Objectives The present study examined fitness levels using five components of health-related fitness in Saudi students aged 10–17 years (fat-to-lean mass ratio, cardiorespiratory endurance, upper body strength and endurance, abdominal muscle strength and endurance, and flexibility). Subsequently, the association between BMI and a health-related fitness index (HR-PFI) based on the five fitness components was investigated. Methods The study was conducted on 1,291 students with a mean age of 12.95 ± 1.72 years. Participants included 1,030 boys aged 12.80 ± 1.79 years, with 479 young boys (11.24 ± 0.81b years), and 551 adolescents (14.16 ± 1.21 years). Moreover, the study examined 261 girls averaging 13.54 ± 1.2 years old, with 66 young girls (11.92 ± 0.27 years), and 195 teenage girls (14.09 ± 0.85 years). Each participant's health-related fitness level was assessed by the following tests: Bioelectrical Impedance Analyzer (BIA) for body composition, one-mile run/walk test for cardiorespiratory endurance, curl-up test for abdominal muscle strength and endurance (AMSE), push-up test for upper body strength and endurance (UBSE), and back-saver sit-and-reach test for flexibility. Results The overall prevalence of overweight and obesity was 10.4 and 24.7% in boys and 10 and 8.4% in girls, respectively. The mean Z-scores of performances decreased from the underweight to the obese groups. BMI was positively associated with the ratio of fat mass to lean mass and negatively associated with cardiorespiratory endurance in the overall group of participants as well as in the subgroups by sex and age categories. BMI was also negatively associated with flexibility and HR-PFI in the total group, UBSE, AMSE, and HR-PFI in prepubertal boys, and UBSE in prepubertal girls. The coefficient of determination values was 0.65 in the total group, 0.72 in prepubertal boys, 0.863 in adolescent boys, 0.956 in prepubertal girls, and 0.818 in adolescent girls. Conclusions Overall health-related physical fitness, fat-to-lean mass ratio, and cardiorespiratory endurance are the factors that most affect BMI in Saudi students aged 10 to 17.